CAPTOPRIL INCREASES ENDOTHELIN SERUM CONCENTRATIONS AND PRESERVES INTESTINAL-MUCOSA AFTER MESENTERIC ISCHEMIA-REPERFUSION INJURY - (:unkn) unknown (SPRINGER, 1994)
Endothelial cells modulate the tone of the underlying smooth muscle by generating endothelium-derived relaxing and constricting factors. Captopril (CPT), unlike other angiotensin-converting enzyme (ACE) inhibitors, contains a sulfhydryl (-SH) group and can act as a free radical scavenger. Iloprost (ILO) is a synthetic analogue of prostacyclin and mimics the effects of this compound. This study was designed to investigate the effect of ILO and CPT on the mechanism of endothelin (ET) release after mesenteric ischemia-reperfusion (I/R) injury in the rat. Sprague-Dawley rats were divided into five groups: sham-operated, control, ILO (25 mu g/kg), CPT (10 mu g/kg), and ILO+CPT. The superior mesenteric artery was occluded for 30 min and then allowed 90 min of reperfusion, except in the sham-operated group, and the corresponding agents were given to the treated groups prior to UR injury. After I/R injury, portal venous blood was obtained for ET assay, and ileal tissue samples were also obtained for the determination of malondialdehyde (MDA), prostaglandin E(2) (PGE(2)) and leukotriene C-4 (LTC(4)) and for histopathological examination. MDA levels were significantly lower in the CPT, ILO and, ILO+CPT groups than in the control group, indicating the inhibition of lipid peroxidation in all groups. ET levels increased in the control group, and this increase was reversed with ILO. In the CPT group, ET levels were significantly increased, and the addition of ILO did not affect this increase. Significant cytopreservative effect was achieved with ILO and CPT, the latter being more prominent histopathologically. CPT exerts a significant protective effect on the intestinal mucosa after I/R injury. This protection is accomplished by increased ET levels and seems to be unrelated to its inhibitory effect on lipid peroxidation and also unrelated to the arachidonic acid cascade.
Keywords: INTESTINAL; ISCHEMIA REPERFUSION INJURY; MALONDIALDEHYDE; LIPID PEROXIDATION; ENDOTHELIN; SUPEROXIDE-DISMUTASE; CELLULAR BIOLOGY; RELAXING FACTOR; RADICALS; RECEPTORS; RAT; PROSTACYCLIN; MYOCARDIUM; ILOPROST; CLONING